MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA PAPAN MULTIFUNGSI PADA MATERI KELIPATAN PERSEKUTUAN TERKECIL DAN FAKTOR PERSEKUTUAN TERBESAR KELAS IV - Adria Adria; Lian G. Otaya; Miftha Huljannah (Al-mujahidah, 2026)
This study aims to determine how the use of multifunctional board media can improve learning outcomes in the material of Least Common Multiples and Greatest Common Factors of grade IV SDN 21 Limboto, Gorontalo Regency. The subjects in this study were 1 class teacher and 26 grade IV students of SDN 21 LIMBOTO. The object of this study was the use of Musi Board Media to improve student learning outcomes in learning. Data collection techniques used were observation, tests and documentation. Based on the results of the study, it can be concluded that the use of multifunctional board media can improve student learning outcomes. In cycle I, the percentage of classical student learning completion only reached 53.84%, while in cycle II it increased significantly to 92.30%. This shows that multifunctional board media is able to help students understand the concept of Least Common Multiples and Greatest Common Factors concretely through the activities of moving, grouping, and comparing numbers directly on the board. Student learning activities also increased in each cycle.